The Future of Coaching: A Conceptual Framework for the Coaching Sector From Personal Craft to Scientific Process and the Implications for Practice and Research - Passmore, Jonathan; Evans-Krimme, Rosie (Frontiers in Psychology, 2021)
This conceptual paper explores the development of coaching, as an expression of applied positive psychology. It argues that coaching is a positive psychology dialogue which has probably existed since the emergence of sophisticated forms of language, but only in the past few thousand years has evidence emerged of its use as a deliberate practice to enhance learning. In the past 50 years this dialectical tool has been professionalized, through the emergence of professional bodies, and the introduction of training and certification. We have used Rostow’s model of sector development to reflect on future possible pathways to explore coaching’s development, comparing it with the development of two other sectors, agricultural and clothing sectors, to understand possible futures. We have offered a five-stage model to conceptualise this pathway of development. Using this insight, we have further reviewed past research and predicted future pathways for coaching research, based on a new eight-phase model of coaching research.